Language shift among Javanese youth and their perception of local and national identities - Erna Andriyanti (Penerbit Universiti Kebangsaan Malaysia, 2019)
It is not uncommon for language to play an important role in identity issues in multilingual countries. Declaring one of the important community languages as the official language in such a country can pose a threat to the survival of the other languages. Bahasa Indonesia is an example of this phenomenon. Its successful establishment as the national language has altered the local language situation throughout the country. Relevant to this study, it has had an important effect on young people’s use of Javanese, the dominant local language of Yogyakarta. This study analyses the extent of language shift among the young multilinguals in the city and investigates the youth’s search for authentic local and national identities. A questionnaire was used to elicit the youth’s mother tongue as well as their attitudes and perceptions towards Javanese and Bahasa Indonesia and local and national identities. Their real use of languages was obtained through non-participative observations. A sample group of 1,039 students from 10 junior and senior high schools was surveyed. The findings reveal the current status of Javanese and Bahasa Indonesia as mother tongues and the identitylanguage choice links. Most young people with Javanese parents claimed that Bahasa Indonesia is their first language. This signals a weakened intergenerational transmission of Javanese. With regard to identity, the youth’s sense of national identity is stronger than their sense of local identity. To elevate the vitality of Javanese and strengthen the local identity, intergenerational transmission and intensive use of Javanese at school is imperative.